Study on Lavender Essential Oil Chemical Compositions by GC-MS and Improved pGC - Dong, Guangyao (Molecules, 2020)
Lavender essential oil from the aerial parts of Lavandula angustifolia Mill. was analyzed by GC-MS equipped with three capillary columns of different polarities, which were HP-1, HP-5 ms and HP-INNOWax. A total of 40 compounds were identified by GC-MS, accounting for 92.03% of the total essential oil compositions. Nineteen monomers were separated by column chromatography and improved preparative gas chromatography (pGC), six of which could not be retrieved from the NIST 14 (National Institute of Standards and Technology, USA; 14th edition) library database. Fifteen compounds were identified for the first time in lavender essential oil. The improved pGC not only doubled the efficiency but also greatly reduced the cost.